Dampak Ekonomi Makro terhadap Inward Forect Direct Investment (FDI) di Indonesia - Muhammad Ubaidillah Al Mustofa; Imron Mawardi; Tika Widiastuti; Raditya Sukmana; Tony Hanoraga; Khairun Nisa; Puput Rosita Febrianti (Jurnal Sosial Humaniora, 2024)
This paper investigates the country-specific risks associated with inwardforeign direct investment (FDI) in Indonesia and analyzes the broadermacroeconomic consequences. The study utilizes the AutoregressiveDistributed Lag (ARDL) model to examine both the short-term and long-termcointegration between macroeconomic factors and foreign investmentinflows. The research is based on secondary annual time series data from1984 to 2015. In the short term, the exchange rate has a crucial impact, asdepreciation of the Indonesian Rupiah leads to a higher inflow of FDI.However, while financial variables do not significantly affect the dependentvariable in the long term, independent variables such as inflation, GDPgrowth risk, and economic and political risks do have a considerable effect.Rational foreign investors prioritize maximizing returns on their investmentsby closely monitoring the volatility of macroeconomic conditions. Thus, it isimperative for the government to regulate these aspects to enhance the inflowof foreign investments.